2005
DOI: 10.1093/nar/gki574
|View full text |Cite
|
Sign up to set email alerts
|

Unusual features of fibrillarin cDNA and gene structure in Euglena gracilis: evolutionary conservation of core proteins and structural predictions for methylation-guide box C/D snoRNPs throughout the domain Eucarya

Abstract: Box C/D ribonucleoprotein (RNP) particles mediate O2′-methylation of rRNA and other cellular RNA species. In higher eukaryotic taxa, these RNPs are more complex than their archaeal counterparts, containing four core protein components (Snu13p, Nop56p, Nop58p and fibrillarin) compared with three in Archaea. This increase in complexity raises questions about the evolutionary emergence of the eukaryote-specific proteins and structural conservation in these RNPs throughout the eukaryotic domain. In protists, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Although the SL region may be occasionally lacking in nuclear-encoded mRNAs in E. gracilis [9], its absence from the transcripts investigated here indicates that they likely originated exclusively in the plastid. Our experiments also confirmed that a small portion of these mRNAs is polyadenylated, since they could be amplified with gene-specific primers and cDNA prepared using oligo(dT) primer.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the SL region may be occasionally lacking in nuclear-encoded mRNAs in E. gracilis [9], its absence from the transcripts investigated here indicates that they likely originated exclusively in the plastid. Our experiments also confirmed that a small portion of these mRNAs is polyadenylated, since they could be amplified with gene-specific primers and cDNA prepared using oligo(dT) primer.…”
Section: Discussionmentioning
confidence: 67%
“…Similar to nuclear cis-splicing, trans-splicing process is also mediated by spliceosomes, but a Y-branch intron structure is formed instead of a lariat [8]. The only currently known nuclear mRNA lacking the SL sequence in E. gracilis is that of the fibrillarin gene [9]. Since SL-trans-splicing does not occur in organelles (mitochondria, plastids), the presence (or absence) of an SL sequence at the 5 0 -end of a euglenozoan mRNA is diagnostic for its synthesis in the nucleus (or organelles, respectively).…”
mentioning
confidence: 99%
“…The snoRNAs are guide RNAs that base-pair with the substrate to specify the site of modification; a few of each class also or instead similarly determine cleavage sites in pre-mRNA. They are absent in eubacteria, but found in archaebacteria, the sisters of eukaryotes (where they are called small (s) RNPs as they have no nucleolus), and thus were already present in the ancestral eukaryote host when the eubacterial ancestor of mitochondria was enslaved, as was fibrillarin a key nucleolar protein that is the C/D snRNP methyl transferase and Cbf5 the H/ACA pseudouridine synthetase (Reichow et al 2007), as well as relatives of the other protein components of C/D snRNPs (Russell et al 2005). The archaebacterial character of euglenozoan snoRNAs (both in trypanosomatids and Euglena) is most evident for the H/ACA class, which in both groups consist of single (or rarely triple) stem loops (Doniger et al 2009;Moore and Russell 2012), whereas in neokaryotes they are all double stem loops (Luo et al 2009).…”
Section: Position Of Loukozoa On the Eukaryote Treementioning
confidence: 99%
“…The non-conventional introns are defined as containing extensive secondary structural potential via base-pairing of intron 5′ and 3′ end proximal sequences, but little overall intron sequence conservation (Tessier et al 1991;Canaday et al 2001;Russell et al 2005;Milanowski et al 2014Milanowski et al , 2016Schwartzbach 1992, 1994) (Fig. 8.1b).…”
Section: Nuclear-encoded Intronsmentioning
confidence: 99%
“…Additionally, some of the predicted spliceosomal introns show extended base-pairing potential in intron locations similar to regions of secondary structure observed in the non-conventional introns. Such observations have raised questions about whether interconversion between intron classes may occur during intron sequence evolution in Euglena and whether introns demonstrating mixed features of both classes should be classified as a distinct type called "intermediate" introns (Canaday et al 2001;Russell et al 2005). These could potentially be excised using components of both the spliceosome and trans-acting non-conventional intron splicing factors.…”
Section: Nuclear-encoded Intronsmentioning
confidence: 99%